2018
DOI: 10.1101/352559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer stemness, intratumoral heterogeneity, and immune response across cancers

Abstract: Regulatory programs that control the function of stem cells are active in cancer and confer properties that promote progression and therapy resistance. However, the impact of a stem cell-like tumor phenotype ("stemness") on the immunological properties of cancer has not been systematically explored. Using gene expression-based metrics, we evaluate the association of stemness with immune cell infiltration and genomic, transcriptomic, and clinical parameters across 21 solid cancers. We find pervasive negative as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
110
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(130 citation statements)
references
References 85 publications
19
110
1
Order By: Relevance
“…Collectively, these results indicate that the high DEPTH ITH level is likely associated with worse clinical outcomes in cancer. This is consistent with previous studies showing that ITH was an adverse prognostic factor 11 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Collectively, these results indicate that the high DEPTH ITH level is likely associated with worse clinical outcomes in cancer. This is consistent with previous studies showing that ITH was an adverse prognostic factor 11 .…”
Section: Resultssupporting
confidence: 94%
“…3g ). Tumor stem cell-associated characteristics (“stemness”) are associated with ITH and poor outcomes in cancer 11 . Interestingly, we observed significant positive correlations between DEPTH scores and tumor stemness scores in pan-cancer ( p = 4.86 × 10 −52 , ρ = 0.16) and in 20 individual cancer types (FDR sp < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the DEGs play a vital role in regulating the ccRCC microenvironment, and could influence ccRCC development. Previous studies have suggested that the immune response contributes to tumor progression and drug resistance of various cancers (Astaneh, Dashti, & Esfahani, ; Miranda et al, ; Pitt et al, ), including bladder (Flores‐Martín et al, ; Holland et al, ), lung (Hays & Bonavida, ; Sorich, Rowland, Karapetis, & Hopkins, ), and breast cancers (Wagner et al, ). The results of the KEGG enrichment analyses suggested that the DEGs were mostly enriched in cytokine‒cytokine receptor interaction, hematopoietic cell lineage, primary immunodeficiency, chemokine signaling pathway, steroid hormone biosynthesis, and intestinal immune network for IgA production.…”
Section: Discussionmentioning
confidence: 99%
“…treatment response between tumors with and withoutTSCs were highlighted in this work, such as elevated intra-tumor heterogeneity and mixing. The stemness of a tumor has been experimentally associated with enhanced heterogeneity and treatment resistance[39,40].We observe that the tumor invasion is mostly driven close to the surface of the tumor and can investigate the changing tumor composition over time. In some simulation regimes, rare events influence not only details of the individual simulation but can influence the macroscopic , such as the resurgence of tumors post-treatment.This improved theoretical understanding of cancer growth as emerging behavior opens new research avenues.…”
mentioning
confidence: 88%